"Apparent" heart failure: a syndrome caused by renal artery stenoses. Issue 2 (1st February 2000) - Missouris, C G; Belli, A-M; MacGregor, G A
Abstract : OBJECTIVE: To report on renal artery stenosis presenting as congestive heart failure. DESIGN: Case series. SETTING: Tertiary referral centre. PATIENTS: Nine hypertensive subjects (five male, four female) seen in the blood pressure unit, St George's Hospital, between 1991 and 1997 with clinical signs and symptoms of congestive cardiac failure but without overt coronary or valvar heart disease. Mean (SEM) age was 67 (3) years. Eight patients had renal artery revascularisation with percutaneous angioplasty and one had surgery. RESULTS: Renal revascularisation was followed by a large fall in blood pressure from 191/94 (7/3) to 150/75 (8/5) mm Hg two days after intervention (p < 0.01). There was also a large natriuresis and weight reduction. One week after revascularisation there was a mean loss in weight of 3.8 (0.6) kg. The largest fall in weight was seen in those patients with stenosis in a single functioning kidney. Furthermore, plasma atrial natriuretic factor fell from 120 (28) to 48 (9) pg/ml (p < 0.05; n = 6; normal value = 8.6 (0.8) pg/ml), and serum creatinine fell from 200 (37) to 140 (11) μmol/l (p < 0.025). The clinical signs and symptoms of heart failure resolved and the diuretics were then withdrawn in all patients. On long term follow up, patients remained free from symptoms and signs of heart failure and the blood pressure was better controlled. CONCLUSIONS: In hypertensive patients with symptoms and signs of congestive heart failure who do not have obvious ischaemic or valvar heart disease, renal artery stenosis should be considered as a possible underlying cause. Relief of the stenosis can result in resolution of the apparent heart failure.